Adaptation of indigenous traditional performance to a tourism entertainment: a case study of Hmong People in Ban Mae Sa Mai, Thailand / Wirasant Wirunsakunphiban ... [et al.] - Wirunsakunphiban, Wirasant; Nusen, Rachod; Abu Bakar, Ayu Haswida; Jonathan Linggang, Duratul Ain Dorothy (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The Hmong are the second largest hilltribe group in Thailand. They migrated from China to the northern part of Thailand today during the nineteenth century. The Hmong have their own unique culture. Now they often use culture to promote tourism. Some of them live in Ban Mae Sa Mai, a Hmong community in Chiang Mai which is known for its traditional culture performance, handicrafts, and costumes. The Hmong in this community demonstrated traditional shows for visitors. The shows are only available with a request in advance. On this note, the purpose of this study is to explore the Hmong traditional culture shows for the tourists. Focusing on the adaptation process occurred between the original version of this traditional performance and the one presented to the tourists. The research objective that will be discussed is to identify and explore the adaptation process through selected elements in the Hmong shows presented to the tourists as a commercial art piece. It is qualitative research with an emphasis on observation, interview and video recording. This study uses Poetic Method by Aristotle as instruments to select elements in the shows for data analysis and uses Cohen's contrariety of ethnic tourism to explain the changes in the ethic shows.